Reducibility analysis Cu-Zn based catalysts for methanol synthesis via CO2 hydrogenation reaction / Siti Aisyah Munirah Razali and Dr. Muhammad Zahiruddin Ramli - Razali, Siti Aisyah Munirah; Ramli, Muhammad Zahiruddin (2020)
Greenhouse effect has always been a major concern in environment. One of the factors greenhouse effect is global warming. The rapid rate of global warming can raise the level of temperature in the atmosphere, thus producing gases which eventually would be a harmful substance for world’s ecosystem. Carbon dioxide (CO2) hydrogenation for methanol synthesis is one of the common methods to reduce the emission. Therefore, the objective of this study is to prepare and characterize a various formulation of Cu-Zn based catalysts. Also investigate of reducibility behavior of Cu-Zn based catalysts and its relation towards methanol synthesis via CO2 hydrogenation reaction. In this process, co –precipitation method are being applied to prepare the catalyst formulation. Three different types of catalyst which is CZZ, CZA and CZAZ are used in this experiment with same ratio of Cu-Zn and various ratios for promoters in each formulation. BET analysis is performed alongside in order to study the characteristic of surface area and pore distribution of the catalyst. As a result, CZAZ has higher BET surface area while resulted in lowest in pore volume and pore size. Normally, the reduction analysis is performed by using temperature programmed reduction (TPR). This method used to analyses and highlights the reduction profile of various formulation of catalyst. Based on the results shown, all catalyst used has performed an accurate result which is one peak of broad reduction profile with H2 consumption quantity at maximum temperature. Hence, the addition of promoters such as Al, Zr affected the Cu dispersion in the catalyst thus reduction behavior of the catalysts was observed. CZAZ resulted to be the most effective catalysts observed in TPR analysis with lower maximum temperature 194.48oC and higher quantity of H2 consumption for 4.63%. Consequently, it also produced most CO2 conversion and CH3OH selectivity in the process reaction simultaneously generating higher yield compares to others proposed samples. It is believed that the improved performance of methanol synthesis are largely affected by the active site that available in the catalyst which enable Cu reduce more for exhibits the best yield in the process reaction.